Fluoroscence Angiography for Assessment of Gastric Conduit: Initial Experience from a Tertiary Care Center - Thakur, Binay; Li, Aiming; Devkota, Mukti; Chaudhary, Manish; Regmi, Yogesh (Nepalese Journal of Cancer, 2019)
Introduction: Anastomotic leak (AL) after surgery for esophageal cancer remains a main cause of postoperative morbidity and mortality. Poor tissue perfusion at the site of anastomosis is one of the major factors for leak. We aimed to review the results of Indocyanine Green dye (ICG) with a goal to decrease the leak rate.Methods: Patients with cancer of esophagus and gastroesophageal junction were subjected to either upfront surgery or preoperative chemoradiation/ chemotherapy followed by surgery. Stomach was used for reconstruction. Intravenous injection of 5 mg – 10 mg ICG was given and vascular perfusion was assessed with infrared light of laparoscopic telescope. Gastroesophageal anastomosis was made at the site of adequate ICG perfusion. These patients (ICG group) was compared to the other group of patients in whom ICG was not used (Non-ICG group).Results: 28 and 396 patients belonged to ICG and Non-ICG group, respectively. 61% in ICG group and 32% in Non-ICG group had preoperative treatment (p